Pengaruh Pemberian Paclobutrazol dan Pupuk Fosfor terhadap Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea Mays var Saccharata Sturt.) - Deni Martogi Sitinjak; Nurbaiti Nurbaiti; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of paclobutrazol and phosphorus fertilizer application on sweet corn growth and yield. This research was conducted at experimental farm, the Faculty of Agriculture, University of Riau, Tampan, Pekanbaru, from September to December 2016. This study were using a randomized block design (RAK) factorial consisting of two factors: The first factor is the concentration of paclobutrazol which consists of 4 levels (0 ppm, 500 ppm, 1000 ppm and 1500 ppm) andthe second factor is the dose of phosphorus fertilizer (200 kg / ha, 300 kg / ha and 400 kg / ha)with three replications. Parameters were measured in this research was plant height, harvest age, weight ofhusked cob, weight of cob without husk, cob diameter, number of grain rows per ear, number of grains per ear and the production per m2. Interaction ofpaclobutrazol and phosphorus fertilizers gave no significant effect on all parameters. Application ofpaclobutrazol significantly affected all parameters except number of seed rows per ear. Phosphorus fertilizer significantly affected the number of seeds per row cob and production per m2. Application of 1000 ppm Paclobutrazol and phosphorus fertilizer to 300 kg / ha produce sweet corn yield per m2 of 15.11 tonnes / ha. Keywords: corn,paclobutrazol, phosphorus, growth and yield